Talent Identification in Track and Field Throwing Events: Biological Determinants, Future Directions, and a Foresight Approach - Rahmani, Ali; Naderi Nasab, Mehdi; Kalhor, Hossein; Biniaz, Abbas; Nobakht Ramezani, Zahra (Journal of Foresight and Health Governance, 2026)
Talent identification in track and field throwing events remains one of the most difficult challenges in youth sport because early performance can be inflated by maturation, body size, and training opportunity rather than by long-term performance potential. At the same time, the throwing disciplines shot put, discus, hammer throw, and javelin depend on a distinctive cluster of biological characteristics that make them attractive targets for scientific screening. This narrative review examines the evidence on biological determinants of throwing performance and then connects that evidence to future directions in talent identification and to a foresight-oriented model for athlete development. The review argues that anthropometry, lean mass, explosive strength, reactive power, rate of force development, and event-specific coordination are all important, but none should be interpreted in isolation. Instead, those indicators should be read against developmental confounders such as biological maturation and relative age. The literature consistently shows that junior success has weak predictive value for senior excellence and that early talent-promotion systems often reward short-term advantage more than long-term potential. Accordingly, this article proposes that talent identification in throwing should move away from one-time selection batteries and toward longitudinal, multidimensional athlete profiling. A foresight approach is especially useful because it reframes talent identification as a process of managing uncertainty rather than claiming certainty about the future. Such a model encourages repeated monitoring, data integration, fairness-aware interpretation, and ethical caution regarding body composition surveillance and genetic testing. The review concludes that future-ready throwing pathways should seek not to identify a finished champion in adolescence, but to recognize adaptable developmental potential across time and context.